Acute Polychlorinated Biphenyl Benthic Invertebrate Toxicity Testing to Support the 2017 Chronic Dose–Response Sediment Injury Model. (10th March 2021) - Finkelstein, Kenneth; Wirth, Edward F.; Chung, K.W.; Shaddrix, B.S.; Pisarski, E.C.; Rios, C.
Abstract: As managers and decision makers evaluate pollutant risk, it is critical that we are able to measure an assessment of the injury. Often, these estimates are difficult to determine for benthic organisms, so in 2017 a chronic polychlorinated biphenyl (PCB) sediment dose–response model to predict benthic invertebrate injury was proposed. Given both natural resource trustee and consultant questions following publication concerning that the aqueous chronic toxicity testing data used in the 2017 model development were primarily from the 1970s and 1980s, this follow‐up short communication is meant to provide the user some additional data that are more recent. With the advances in analytical and quantitative environmental chemistry (i.e., better detection limits and congener separation), we chose to complete acute aquatic toxicity testing using 3 estuarine invertebrates and lethal endpoints (20 and 50% lethal concentrations). This acute testing was selected because chronic aquatic testing for PCBs outside of the data used in the 2017 study was not available to us. The aquatic results used in the present study were changed to sediment using equilibrium partitioning, as done in the 2017 chronic model, after using the same organic–carbon partition coefficient and total organic carbon for our equilibrium partitioning (EqP)–measured calculations. Based on these acute aquatic toxicity results and a general acute‐to‐chronic injury concentration ratio of approximately 10, we found that the 2017 model was valid and, hence, that a 1.0 µg/g chronic PCB sediment criterion is a reasonable estimation of potential benthic invertebrate injury. This was followed by spiked sediment tests where percent acute sediment injury was compared to the EqP‐ derived chronic value and the results from 2017; modest agreement is shown. Environ Toxicol Chem 2021;40:1188–1193. Published 2020. This article is a U.S. Government work and is in the public domain in the USA.